2011
DOI: 10.1007/s10530-011-9988-8
|View full text |Cite
|
Sign up to set email alerts
|

Could phenotypic plasticity limit an invasive species? Incomplete reversibility of mid-winter deacclimation in emerald ash borer

Abstract: The emerald ash borer (Agrilus planipennis, Coleoptera: Buprestidae) is a wood-boring invasive pest devastating North American ash (Fraxinus spp.). A. planipennis overwinters primarily as a freezeavoiding prepupa within the outer xylem or inner bark of the host tree. The range of this species is expanding outward from its presumed introduction point in southwestern Michigan. We hypothesized that loss of cold tolerance in response to mid-winter warm spells could limit survival and northern distribution of A. pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 54 publications
2
46
0
Order By: Relevance
“…Storage under FTs also holds applications for mass-rearing of insects for pollination (98,124) and potential applications for sterile insect technique (21). FTs could also be exploited to deacclimate insects (103), and thus to reduce cold tolerance of pests as part of a thermal quarantine procedure. Similarly, the negative impacts of repeated cold or heat stress (80) could be leveraged to control stored product pests (59), but this has not been well-explored.…”
Section: Applications and Implications Of Fts Exploiting The Protectimentioning
confidence: 99%
See 2 more Smart Citations
“…Storage under FTs also holds applications for mass-rearing of insects for pollination (98,124) and potential applications for sterile insect technique (21). FTs could also be exploited to deacclimate insects (103), and thus to reduce cold tolerance of pests as part of a thermal quarantine procedure. Similarly, the negative impacts of repeated cold or heat stress (80) could be leveraged to control stored product pests (59), but this has not been well-explored.…”
Section: Applications and Implications Of Fts Exploiting The Protectimentioning
confidence: 99%
“…Interestingly, the benefits of FTs appear to apply only to freezeavoiding and chill-susceptible species: repeated freeze-thaw is damaging to freeze tolerant species (80). In addition, long warming interruptions can lead to deacclimation and loss of cold tolerance (103,113). For example, overwintering emerald ash borer (Agrilus planipennis) prepupae irreversibly lost their cold tolerance after exposure to +10°C for more than a week, reducing survival of subsequent cold exposures (103).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…mid-winter thaws). For example, Sobek-Swant et al (2012) found that winter-acclimatized freezeavoidant emerald ash borer prepupae had increased SCPs and decreased glycerol concentrations after exposure to mid-winter warm spells (+10 and +15 °C), and that this deacclimation was not reversed when the prepupae were returned to -10 °C. Deacclimation is rarely included in cold tolerance studies, but is clearly relevant when attempting to understand the plasticity of cold tolerance, particularly in relation to variable environments.…”
Section: Acclimation Deacclimation and Acclimatizationmentioning
confidence: 99%
“…This holding time allowed minor injuries from extraction to become visible, but was not long enough for the overwintering larvae to lose cold acclimation [27].…”
Section: Introductionmentioning
confidence: 99%